Planet hero: uncovering how to save our earth - Fadzill, Sabrina Mohamad; Daud, Derwina (School of Mechanical Engineering, 2025)
In this digitalization era, e-books are gaining more popularity in the market due to their convenience that includes accessibility, flexibility, and cost-effectiveness. Nonetheless, there is only a small number of e-books that focus on climate change in Malaysia. Even if there is an e-book or physical book that covers such topic, the contents can be hard for children to grasp because of the usage of the words, which are facts that can be tiring and boring for children to read. Hence, this invention will be suitable for children as the e-book is full of colorful illustrations, and contents that are exciting and related to the subject, thus, making it suitable for children to understand difficult topics. Notably, arts help people associate with difficult subjects such as climate change on a personal and emotional level, making it more applicable to their daily lives or the community (Bentz et. al., 2021). Additionally, this e-book can successfully capture children’s attention as well as acquire new knowledge at the same time. Moreover, this e-book can be incorporated into school curriculums as educational resources for children to learn at school and simultaneously can be used by parents to cultivate the love of reading at an early age for their children